Constraints in Geographic Information Systems Learning Across Senior High Schools in Metro City - Alifia, Lisa Nur; Utami, Dian; Wijaya, Nyokro Mukti; Istiawati, Novia Fitri (Universitas Lampung, 2026)
The study aims to analyze the constraints in the implementation of Geographic Information Systems (GIS) learning across three senior high schools in Metro City. A qualitative approach with a multi-site design was employed. Data were collected through interviews, observations, and documentation, then analyzed using cross-site analysis techniques. The findings indicate that teachers generally possess basic conceptual knowledge but face limitations in technical skills and access to continuous training. As a result, instructional strategies remain largely lecture-based, with minimal integration of technology. Students experience difficulties in understanding GIS concepts and show relatively low engagement due to the lack of practical activities. In addition, limitations in facilities, software availability, infrastructure, and institutional support further hinder effective implementation. This study concludes that GIS learning challenges are systemic and require integrated efforts, including improving teacher competence, enhancing training programs, promoting interactive learning strategies, and strengthening institutional support.